The making of a policeman: a social history of a labour force metropolitan London, 1829-1914 - Shpayer-Makov, Haia (Ashgate, 2002)
Machine generated contents note: Introduction 1 -- Part One: Creating a Portrait of a Policeman 23 -- 1 Personal Motives and Formal Selection Criteria 25 -- 2 Informal Selection Preferences and the Response of Labour: Augmenting the Portrait 43 -- 3 Job Stability vs. Mobility: Rounding Out the Portrait 77 --Part Two: Control and Accommodation 95 -- 4 Socialization, Bureaucracy and Everyday Life in the Force 97 -- 5 The Paternalist Contract: Labour-Management Reciprocity 153 -- 6 Patterns of Promotion 189 -- 7 Recreation and Control 215 -- 8 Conflict and Negotiation: Industrial Relations Without Unionization 245